2018
DOI: 10.1063/1.5010951
|View full text |Cite
|
Sign up to set email alerts
|

Perovskite-based solar cells with inorganic inverted hybrid planar heterojunction structure

Abstract: We demonstrated the good performance of inorganic inverted CH3NH3PbI3 perovskite-based solar cells (SCs) with glass/ITO/NiOx/CH3NH3PbI3 perovskite/C60/ room temperature (RT)-sputtered ZnO/Al structure. We adopted spin coating and RT sputtering for the deposition of NiOx and ZnO, respectively. The inorganic hole and electron transport layer of NiOx and RT-sputtered ZnO, respectively, could improve the open-circuit voltage (VOC), short-circuit current density (JSC), and power conversion efficiency (η%) of the SC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 45 publications
3
5
0
Order By: Relevance
“…A further potential explanation is an enhanced electron blocking by the sputtered NiO x HTLs. Such an improved electronic injection barrier can be attributed to a NiO x conduction band above the lowest unoccupied molecular orbital of PEDOT:PSS as previously reported in organic photovoltaics. , The significant reduction in the dark current level observed in this study is consistent with dark current characteristics reported for perovskite devices based on solution processed NiO x and PEDOT:PSS HTLs. , Although the level of the dark current in flexible X-ray detectors is significantly reduced by NiO x HTLs as well, the effect is less pronounced compared to the rigid detectors realized on glass substrates. However, we note that the flexible detectors investigated within this study are based on bottom electrodes fully composed of solution processed c-PEDOT:PSS while the glass substrates are coated with ITO.…”
Section: Resultssupporting
confidence: 91%
“…A further potential explanation is an enhanced electron blocking by the sputtered NiO x HTLs. Such an improved electronic injection barrier can be attributed to a NiO x conduction band above the lowest unoccupied molecular orbital of PEDOT:PSS as previously reported in organic photovoltaics. , The significant reduction in the dark current level observed in this study is consistent with dark current characteristics reported for perovskite devices based on solution processed NiO x and PEDOT:PSS HTLs. , Although the level of the dark current in flexible X-ray detectors is significantly reduced by NiO x HTLs as well, the effect is less pronounced compared to the rigid detectors realized on glass substrates. However, we note that the flexible detectors investigated within this study are based on bottom electrodes fully composed of solution processed c-PEDOT:PSS while the glass substrates are coated with ITO.…”
Section: Resultssupporting
confidence: 91%
“…The series resistance is determined by fitting the Nyquist plots (see Supporting Information S2) and is found to be below 20 Ω cm 2 throughout the bromide to iodide ratios used in this study. The dark IV curves presented here are consistent with those found in the literature for devices with similar perovskite and transport materials …”
Section: Resultssupporting
confidence: 90%
“…The dark IV curves presented here are consistent with those found in the literature for devices with similar perovskite and transport materials. 22 …”
Section: Resultsmentioning
confidence: 99%
“…As a first consistency check, we compared the material candidates in figures 3(a) and b to materials that have already been used as transport or mesoporous scaffold layers in PSCs. We found that our search is consistent with common materials such as: NiO [25,52] and PbO [53,54] as intrinsic HTMs in PSCs, as well as ZnO [52] and TiO 2 [38] as electron-transporting materials (ETMs). Similarly, our candidate materials included ZrO 2 [39] and Al O 2 3 [55] which are used as mesoporous scaffolds in PSCs.…”
Section: Resultssupporting
confidence: 78%